Risk management in public private partnerships - Mervyn K. Lewis (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2001)
Public Private Partnerships (PPPs) are arrangements wherein private parties participate in, or provide support for, the provision of infrastructure, and a PPP project results in a contract for a private entity to deliver public infrastructure-based services. A fundamental feature is that the government does not own the infrastructure but, rather, contracts to buy infrastructure and related ancillary services from the private sector over time. A common misconception about PPP projects is that they are principally about private sector financing of public infrastructure. This is not strictly correct. Financing is only one element of the calculation. The very essence of a PPP is that the public sector does not primarily buy an asset; it is purchasing a service under specified terms and conditions. This feature provides the key to the viability (or not) of the transaction. A PPP is at base a risk-sharing relationship, in this case to bring about certain desired public policy outcomes. Any project needs to be structured to achieve optimal risk allocation. Value for money is a key facet of the policy and if sufficient risk cannot be transferred to private parties, it is unlikely that a PPP will deliver value for money. At the same time, unloading inappropriate forms of risk merely adds unnecessary cost to a PPP agreement. Only 'efficient' levels of risk should be transferred. Risk management - identification, assessment, allocation and mitigation of risks - is central to determining the success of the project and achieving value for money.
Keywords: 330